Visual Identity of Tlogo Land Tourism to Enhance Brand Awareness - Fernanda, Rico Alan; Wardani, Lely Surya (LPPM STIKI Malang, 2024)
Tlogo Land is a tourist destination in Malang Regency that faces issues with visual identity inconsistency, including the use of different logos across various social media platforms. This study aims to design a consistent and integrated visual identity to enhance brand awareness and attract tourists. The research employs a non-participatory approach, with data collected through direct observation of Tlogo Land and interviews with the management. The process of designing the visual identity follows the Design Thinking method, consisting of five stages: Empathize, Define, Ideate, Prototype, and Test. The results show that the designed visual identity, including the logo, colors, and other graphic elements, effectively reflects the character and values of Tlogo Land as a nature-based tourist destination. The implementation of the visual identity on media such as business cards, staff uniforms, and stamps proves to be effective in increasing recognition and creating a positive image of Tlogo Land among visitors. This study concludes that developing a consistent visual identity can be an effective strategy for brand awareness of tourist destinations, while also strengthening Tlogo Land's image as a professional and attractive tourist destination